Study Of The Function And Meaning of Ruwatan Murwakala: The Value Of Tradition In Sundanese Wayang Golek - Maulana, Marsel Ridky; Sembiring, Piter (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2025)
The wayang golek purwa performance “Ruwatan Murwakala” in Sundanese society is not merely an expression of traditional art but also reflects human awareness of transcendent forces that influence their lives. Additionally, the role of the dalang, or juru brata, is regarded as that of a wise figure capable of providing guidance to the community. This study employs a qualitative approach with ethnographic methods to examine the meaning and function of the “Ruwatan Murwakala” performance. Data collection techniques include direct observation of performances, in-depth interviews with puppeteers and cultural practitioners, and a literature review. The findings indicate that “Ruwatan Murwakala” embodies educational, religious, and philosophical values while also serving to strengthen communal morals and character. Beyond its role as entertainment, the performance functions as a medium for cultural transformation, bridging traditional values with contemporary societal needs. The symbolic elements within the performance convey notions of purity, prosperity, philosophical depth, and spiritual wisdom, reflecting local cultural values. Furthermore, the ritual aspects of “Ruwatan Murwakala” reinforce communal solidarity and the transmission of cultural heritage across generations. In conclusion, this performance not only upholds Sundanese cultural identity but also serves as a universal reflection on human relationships with cosmic forces, demonstrating the ongoing relevance of traditional rituals in modern society.